Boosting Employee Performance through Job Satisfaction in Indonesia: Meningkatkan Kinerja Karyawan melalui Kepuasan Kerja di Indonesia - Putri, Dinda Rizky Ana; Sumartik, (Indonesian Journal of Law and Economics Review, 2024)
This study examines the effects of the work environment, morale, and rewards on employee performance at PT. Air Bersih Jawa Timur (Perseroda), with job satisfaction as an intervening variable. Using a quantitative method and total sampling of 88 employees, data were collected through questionnaires and analyzed with statistical tests and regression analysis using SPSS. Results show that the work environment, morale, and rewards positively impact both job satisfaction and employee performance. Job satisfaction also significantly mediates the relationship between these factors and performance. The findings highlight the importance of a supportive work environment, high morale, and recognition in enhancing employee performance. Highlight: Positive Impact: Work environment, morale, rewards significantly enhance employee performance. Mediation Role: Job satisfaction mediates work factors and performance. Quantitative Analysis: SPSS data from 88 employees validate hypotheses. Keywoard: work environment, morale, rewards, job satisfaction, employee performance